Egyptian Revolution Visualization in Arabic Song Syuhada 25 Yanayer and Sout El Horreya - Muhammad Bakhrul Ilmi (Universitas Ahmad Dahlan, 2023)
This study presents a description of the visual depiction of the revolutionary process, or Tsaurah which is shown in the song clips of Syuhada 25 Yanayer and Sout El Horreya. By using semiotic theory Roland Barthes is able to interpret the signs seen in the clips of the two songs. Details about the Tsaurah incident can be known and examined after watching and analyzing every piece of the video clips of the revolutionary songs. The description of the struggle of the Egyptian people can be seen from two different sides in these two research objects; he looks full of sadness when he sees the visual for the song Syuhada 25 Yanayer, and he looks full of happiness when he sees the clip for the song Sout El Horreya. The study used in this research is descriptive qualitative type. The collection of data in this paper was done by observing and noting. The results of the study show that the two song clips that are the object of study are able to visually depict the conditions during the Revolution in Egypt.